2015
DOI: 10.1111/bju.13176
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of care for metastatic renal cell carcinoma in Australia

Abstract: ObjectiveTo examine the patterns of care and outcomes for metastatic renal cell carcinoma (mRCC) in Australia, where there are limited reimbursed treatment options. In particular, we aim to explore prescribing patterns for first-line systemic treatment, the practice of an initial watchful-waiting approach, and the use of systemic treatments in elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 13 publications
2
17
1
Order By: Relevance
“…In other retrospective series of de novo mRCC patients, mOS varies between 13 and 19 months . Patterns of care and survival outcomes in the full cohort ( n = 212) of this Australian study were previously reported . Notably, the mOS in the overall cohort was 29.1 months, consistent with survival data observed in the phase III studies …”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In other retrospective series of de novo mRCC patients, mOS varies between 13 and 19 months . Patterns of care and survival outcomes in the full cohort ( n = 212) of this Australian study were previously reported . Notably, the mOS in the overall cohort was 29.1 months, consistent with survival data observed in the phase III studies …”
Section: Discussionsupporting
confidence: 86%
“…Our study was approved by the local institutional human research ethics committees. Patterns of care from this cohort have been previously reported …”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…The predominant sequence was TKI‐TKI ( n = 100, 58.8% of 170 patients who received second‐line therapy), followed by TKI‐mTORi ( n = 24, 14.1%) and mTORi‐TKI ( n = 20, 11.8%). Recent real‐world chart review studies carried out in the USA and Australia showed a different treatment sequence of first‐line TKI followed by mTORi (everolimus or temsirolimus) as the predominant second‐line therapy. The present study could be considered to represent the features of systemic mRCC treatment in Japan, as well as the prognosis from TKI treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Information on real‐world treatment patterns and outcomes is informative for clinical practice in this setting, but the information is limited . By studying treatment patterns and outcomes in patients with mRCC, to understand unmet needs, clinical outcomes and the burden of disease after progression from first‐line therapy might be understood.…”
Section: Introductionmentioning
confidence: 99%